An application of the Heckman Selection Model to the Analysis of GIS benefits - Dai, Chunyun (Université d'Ottawa | University of Ottawa, 2017)
Previous studies have identified several characteristics that likely affect the incidence of senior poverty. However, no research addresses the relationship between personal characteristics and the amount of GIS benefits received, which would help to predict directly the demands placed by the senior population on the GIS. In this paper, I expand on the existing literature by using the Heckman two-step selection model to estimate the probability that seniors receive GIS benefits as well as the amount of GIS benefits received, given the senior’s characteristics. The results of the Heckman two-step estimation procedure indicate that selection bias exists. The results also show that seniors who participate in the job market, are highly educated, live in Ontario, are non- immigrants, and speak English have lower probabilities of receiving GIS benefits. In contrast, as age increases, seniors are increasingly likely to receive GIS benefits regardless of the type of household living arrangement, especially seniors who are lone parents, are living with non- relatives only, or are living alone. The marginal effects of gender for the 65 to 69 and 70 to 74 age groups show that men are more likely to receive GIS benefits. This result contradicts those of other researchers. Furthermore, a senior who speaks French only has a higher probability of receiving GIS benefits as age increases. The results of the second-stage equation modelling the amount of annual GIS benefits received fill an existing gap in previous research. The estimates imply that the average predicted annual amounts of GIS annual benefits, conditional on receipt of benefits, are $5,780, $6,011, $4,590, $4,586 and $5,167 for the five age groups considered, respectively. Individuals who had been employed at some time in the past or who have a higher level of education receive on average smaller amounts of GIS benefits, but these effects diminish as age increases. Immigrant status and the type of household living arrangement also affect the amount of benefit received. Seniors who are lone parents, living alone, or immigrants receive more GIS benefits per year, and the impacts of household living arrangements are fairly large. The marginal effects of gender for the 65 to 69 and 70 to 74 age groups show that on average, men receive more GIS benefits than women.